Inclusive and Efficient Value Chains - Meat demand analysis and assessment - Wane, Abdrahmane; Rich, Karl M.; Fall, Abdou (2024)
An assessment of the competitiveness of West African cattle and beef value chains, Evaluate consumer demand for specific beef products and cuts and assess the ability of Sahelian producers to meet those preferences.